Biology, status and management of rice insect pest in Nigeria - Umeh, E.D.N.; Joshi, R.C.; Ukwungwu, M.N. (Elsevier, 1992)
Rice insect pest management in Nigeria is compartmentalized; literature documenting the status of research on the biology and significance of insect pests and on their management, has therefore been reviewed. A holistic, broadly based, multidisciplinary pest-management research approach is suggested. Because of the immense benefits that integrated pest management (IPM) can provide, it is urged that steps be taken immediately to develop and implement IPM for rice insects in Nigeria.